Optimizing the Performance of the Turjawali Unit of the Samapta Unit in Preventing Ordinary Theft to Realize Public Order and Safety (Kamtibmas) in Magelang Police Resort - Filingga Gardaruna (Advances in Police Science Research Journal, 2024)
The number of ordinary theft crimes in Magelang Regency has been increasing since 2019 to 2022. The difficult condition of the community during the pandemic has resulted in people choosing practical ways to gain profit by stealing. The relaxation of health protocols actually increases the potential for theft crimes, so the role of police officers is needed in preventing such problems from happening. This research focuses on the implementation of the performance of the Turjawali Unit of the Samapta Unit and its optimal form in preventing ordinary theft crimes in order to realize public order and safety (kamtibmas) in Magelang Police Resort The research method that used is qualitative descriptive, which is reviewed with the concepts of optimization, patrol, public order and safety (sabhara) concept, and theft crime concept. The theories used in the research are management theory (6M and POAC), SWOT theory, and routine activity theory. The performance implementation of the Turjawali Unit of the Samapta Unit in Magelang Police Resort is analyzed using POAC management theory (Planning, Organizing, Actuating, and Controlling). Then, the optimal form of Turjawali Unit’s performance is analyzed using 6M management theory (Man, Money, Material, Methods, Machine, and Market). The research found that the performance of the Turjawali Unit was not optimal, starting from planning, organizing, implementation, and control, which did not comply with Perkabaharkam No. 1 of 2017. Factors affecting the performance of the Turjawali Unit were analyzed using SWOT theory. It was found that there was a balance between the strengths, opportunities, weaknesses, and threats of the Turjawali Unit of the Samapta Unit in Magelang Police Resort. Efforts to optimize the performance have also not been achieved well because there are still obstacles in the management system of the Turjawali Unit of the Samapta Unit in conducting patrols.It is recommended for the Turjawali Unit of the Samapta Unit in Magelang Police Resort to optimize its performance by maximizing the existing resources through new ideas and innovations, particularly through the development of technology.